Bergman theory induced by a quaternionic perturbed fractional $ψ$-Fueter operator - Cervantes, José O. González; Pérez de la Rosa, Marco A.; Bory Reyes, Juan (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5A useful tool proved in the present paper is the Borel–Pompeiu formula for the resulting function class of null solutions of the quaternionic perturbed fractional $ψ$-Fueter operator. Motivated by this formula, we developed major steps of the associated Bergman theory.